Effect of the liming on the nutrition and the development of the guava root system - Prado, R. D.; Natale, W. (Empresa Brasil Pesq Agropec, 2004)
The application of lime in acid soils improves the plant root system and, consequently, enhances water and nutrients absorption by the plants. The objective of this work was to evaluate the effects of lime application on the development of root system and calcium nutrition of guava plants cultivated in an acid distrofic Red Latosol (Typic Hapludox). Soil samples were collected in four equidistant points, at 75 cm of the trunk and at 0-20 cm and 20-40 cm of depth, in the plots that had received zero (control), 3.7 and 7.4 t ha(-1) of lime. Soil samples were chemically analysed. Lime material was applied at planting, incorporated with grating and moldboard plow. On the second and third years after guava plantation, effects of liming in chemical properties were determined. Forty two months after lime incorporation in the soil (third year of guava plants cultivation), samples of roots were collected with a cylindrical auger, for dry mass and calcium content evaluation. Samples of leaves were also collected. Liming corrected soil acidity increased base saturation and improved calcium availability to plants and, consequently, improved guava root system. Calcium concentrations of 30 mmol(c) dm(-3) in the soil and of 7.5 g kg(-1) in the roots were associated with the highest guava root growth.
Keywords: Psidium guajava; lime; radicel; auger method